Power Control Strategy for Grid-Connected Inverters in Stationary Reference Frame - Lucas S. Xavier; Allan F. Cupertino; Heverton A. Pereira; Victor F. Mendes (Eletrônica de Potência)
The control of grid-connected converters in stationary reference frame has been investigated in several works of literature. One of the challenges of this method is in the computation of the current computing current references as a function of power references. In some works, this issue has been solved based on instantaneous power theory equations described in the stationary reference frame. However, this approach can lead to steady-state errors in the injected power if there is an error in the current control loop, which is the focus of this investigation. Firstly, analytical expressions are derived to investigate the effect of current loop steady-state error in the active and reactive power injected into the grid. Then, this paper proposes a closed-loop power control for grid-connected inverters controlled in the stationary reference frame. This strategy is experimentally investigated in two power conversion system configurations for battery energy storage systems. The results indicate that the proposed scheme guarantees zero steady-state error in the injected power even when the current loop presents an amplitude and phase steady-state error.